EFEKTIFITAS TELENURSING TERHADAP KEPATUHAN MINUM OBAT PADA PASIEN MALARIA DI PUSKESMAS WILAYAH KERJA DINAS KESEHATAN KABUPATEN MIMIKA: Komunitas - Berwulo, Johan; Kusumaningsih, Indriati; Adyatmaka, Andreas (STIKES Bethesda Yakkum, 2020)
Abstract The impact of medication adherence on Malaria patients may increase the concentration of Plasmodium infections in the blood, increase parasitic resistance, disease recurrence, and increase the incidence of malaria. Telenursing interventions are expected to improve compliance with anti-malarial drugs with the Nola Pender health promotion approach to overcome limited regional coverage and utilize communication technology. This study uses Quasi Experimental design with random sampling posttest control group technique. The purpose of this study was to determine the effect of Telenursing on medication adherence to malaria patient at Puskesmas Work Area of ??Mimika Regency Health Office. The sample size of 117 respondents included 88 patients in the intervention group and 29 patients in the control group. Based on Health Promotion of Nola Pender, telenursing is packaged in the form of nursing care for malaria patient in reminding of taking medicine, educating the importance of treatment completely and its effect, perceived grievances and how to overcome them. Results of adherence improvement in the intervention group were 75 (85.2%) of the respondents compared to the control group of 9 (31.0%) respondents. Different independent test pValue = 0,000 (<0.05), there was a difference in medication adherence between the intervention group and the control group. Multivariate test showed there is an effect of telenursing on adherence pvalue = 0,000 (<0.005) OR 9,139. The study recommends that mutual trust between nurse-patient and the use of information technology (telephone / SMS / video call / IVR) can improve health services, especially on providing health education and promotion for patients in difficult to reach areas. Keywords: Telenursing, Medication Adherence, Malaria